Implementasi Projek Penguatan Profil Pelajar Pancasila (P5) di Sekolah Dasar - Aulia Pramita Sari; Erna Zumrotun; Nina Sofiana (Qalam : Jurnal Ilmu Kependidikan, 2023)
This research aims to analyze the implementation of the project to strengthen the profile of Pancasila students in forming the character of students as well as the supporting and inhibiting factors in its implementation. The type of research used is qualitative research. The subjects of this research were students, class IV teachers and principals of SDN 1 Bandung Mayong Jepara. The data collection methods used were observation, interviews and documentation. The results of this research indicate that the implementation of the project to strengthen the profile of Pancasila students at SDN 1 Bandung Mayong has been carried out well. Of the six themes, in the 2022/2023 academic year, even semester, SDN 1 Bandung has implemented one theme, namely "Sustainable Lifestyle. Supporting factors in implementing the project to strengthen the profile of Pancasila students are support from various parties starting from teachers, parents and the surrounding community. Apart from that, students are actively involved in implementing this project. The inhibiting factor in implementing the project to strengthen the profile of Pancasila students is the teacher's lack of understanding of the independent curriculum because P5 is a new breakthrough in the world of education